Where did Hispanic jurors go?: racial and ethnic disenfranchisement in the grand jury and the search for justice - Fukurai, Hiroshi (Western criminology review, 2000)
Past analyses of racial inequality in jury selection exclusively focus on African Americans and their underrepresentation in petit juries. Little research has examined other racial and ethnic minorities such as Hispanic jurors in the grand jury selection system. This paper examines racial and ethnic discrimination and disenfranchisement in the selection of Hispanic grand jurors in California. The study site is Santa Cruz County, California, which has a large Hispanic population but a very small black population, less than one percent, which suggests that most instances of racial and ethnic discrimination in grand jury selection involve Hispanic jurors. The present analysis suggests that the use of the key-man system, along with representative quotas imposed on supervisorial districts after consolidating minority residents into a few districts, effectively limits Hispanic participation on grand jury service, leading to racially and ethnically unrepresentative juries, undermining public confidence in the grand jury system, and further perpetuating the notion of racial discrimination and disenfranchisement in the criminal justice system. Our analysis also points out that California trial judges and jury commissioners still have the discretion to both select and appoint potential jurors to grand juries. Key-man-appointed grand jurors are less likely to be members of racial and ethnic minorities. This practice exists despite the fact that the U.S. Supreme Court has prohibited the use of key-man selection systems for the appointment of grand jurors in federal courts. In order to ensure the placement of Hispanic jurors in the final grand jury, the present paper argues that affirmative action jury selection strategies may be necessary to create racially diverse and ethnically representative grand juries in California.